Using the H-index as a factor in the promotion of surgical faculty - Rongzhi Wang (Heliyon, 2022)
Introduction: Academic productivity is an important determinant for promotion. However, the measurement of academic productivity is ill-defined. The aim of this study is to demonstrate the academic productivity at the time of promotions at our institution. Methods: We reviewed the data of 33 faculty from Department of Surgery at our institution who were promoted from 2006 to 2021. Gender, academic productivity at hiring, and each promotion were obtained. Academic productivity was assessed by bibliometric indices including total number of publications and citations, and H-index, which were obtained from Web of Science. T-test, Mann-Whitney U test, Fisher’s exact test and linear regression analysis were used to assess the association of H-index with length of promotion and gender. P < 0.050 were considered statistically significant. Results: The medians (interquartile ranges) of indexes at hiring, at promotions from assistant professors to associate professors, and from associate professors to full professors were 6.0 (1.5–9.5), 11.0 (9.0–18.0) and 17.0 (9.0–23.0) respectively. A simple linear regression showed significant correlation between the length of promotion to associate professors and their H-indexes at hiring. (F (1, 27) = 10.55, p = 0.003, R2 of 0.281.) There was no statistical significance in the difference of H-indexes at promotions between male and female faculty. Conclusion: At our institution, the median H-indexes at the time of promotions from assistant professor to associate professor and from associate professor to full professor are 11.0 and 17.0. Using the H-index as an objective measure can be a useful tool to junior surgical faculty as reference for applying promotion.